A Review on Promising Membrane Technology Approaches for Heavy Metal Removal from Water and Wastewater to Solve Water Crisis - Mervette El Batouti (MDPI AG, 2021)
Due to the impacts of water scarcity, the world is looking at all possible solutions for decreasing the over-exploitation of finite freshwater resources. Wastewater is one of the most reliable and accessible water supplies. As the population expands, so do industrial, agricultural, and household operations in order to meet man’s enormous demands. These operations generate huge amounts of wastewater, which may be recovered and used for a variety of reasons. Conventional wastewater treatment techniques have had some success in treating effluents for discharge throughout the years. However, advances in wastewater treatment techniques are required to make treated wastewater suitable for industrial, agricultural, and household use. Diverse techniques for removing heavy metal ions from various water and wastewater sources have been described. These treatments can be categorized as adsorption, membrane, chemical, or electric. Membrane technology has been developed as a popular alternative for recovering and reusing water from various water and wastewater sources. This study integrates useful membrane technology techniques for water and wastewater treatment containing heavy metals, with the objective of establishing a low-cost, high-efficiency method as well as ideal production conditions: low-cost, high-efficiency selective membranes, and maximum flexibility and selectivity. Future studies should concentrate on eco-friendly, cost-effective, and long-term materials and procedures.